2012
DOI: 10.1590/s1982-21702012000400008
|View full text |Cite
|
Sign up to set email alerts
|

On the performance of GNSS levelling over steep slopes

Abstract: In geodetic applications variety, one of the main current focuses is recently to determine the heights of ground stations with high accuracy. Specially the possibility of acquiring 3D information of the point positioning with high accuracy is opening up new strategies of investigating the heighting. Global Navigation Satellite System (GNSS) for 3D positioning is undergoing rapid developments and GNSS heighting can be an alternative to terrestrial techniques of height measurements. This paper presents a researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The height differences between the points obtained by the geometric levelling are adopted as reference values and the analysis of the internal and external measurement accuracy is given. In the paper [5], a study of use of the GNSS method for determining height differences in case of steep terrain was presented. In comparison with the results of the geometric and trigonometric levelling, the GNSS method has shown satisfactory accuracy.…”
Section: међународна конференцијаmentioning
confidence: 99%
See 1 more Smart Citation
“…The height differences between the points obtained by the geometric levelling are adopted as reference values and the analysis of the internal and external measurement accuracy is given. In the paper [5], a study of use of the GNSS method for determining height differences in case of steep terrain was presented. In comparison with the results of the geometric and trigonometric levelling, the GNSS method has shown satisfactory accuracy.…”
Section: међународна конференцијаmentioning
confidence: 99%
“…geod., University of Novi Sad, Faculty of Technical Sciences, D. Obradović Square 6, Novi Sad, Serbia, tel: ++381 21 450 810, e -mail: mehmed@uns.ac.rs 4 Igor Sabadoš, dipl.inž. geod., University of Novi Sad, Faculty of Technical Sciences, D. Obradović Square 6, Novi Sad, Serbia, tel: ++381 21 450 810, e -mail: igorsabados@uns.ac.rs 5 Marina Davidović, dipl.inž. geod., University of Novi Sad, Faculty of Technical Sciences, D. Obradović Square 6, Novi Sad, Serbia, tel: ++381 21 450 810, e -mail: marina.davidovic@uns.ac.rs…”
Section: Introductionmentioning
confidence: 99%
“…In the past, several authors have shown that GNSS levelling, i.e., the combination of GNSS height determination and geoid models, is an economic technique for determining physical heights [31][32][33][34][35][36][37]. However, the method itself is limited in two aspects: the accuracy of the ellipsoid height determination and the accuracy of the geoid model.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have claimed that by using GNSS levelling, a height determination accuracy of 1 cm can be achieved [46][47][48]. However, additional studies have shown that it is almost impossible to achieve such an accurate geoid model in mountainous regions [36,49]. The Earth's external gravitational field and is functionals (in addition to the geoid heights of interest and the gravitational anomalies and potential) can be determined using global gravity models (GGMs).…”
Section: Introductionmentioning
confidence: 99%
“…The Global Navigation Satellite System (GNSS), through the use of satellite tracking equipment, allows ellipsoidal heights (h) to be obtained, which, depending on the positioning technique, can reach sub-centimeter accuracies (Erenoglu et al, 2012;Wang, 2013;Scholarin & Awange, 2015;Luna et al, 2017). The determination of these heights, together with geoid undulation values (N, from local or global models), allow the estimation of orthometric heights based on equation (1).…”
Section: Introductionmentioning
confidence: 99%